Exercise Therapy in Type 2 Diabetes Mellitus with Special Emphasis on Running: Effects on Glycemic Control, Metabolic Adaptations, and Psychosocial Outcomes – A Narrative Review - Szczupaj, Maciej; Rudnicki, Jakub; Krzyżanowska, Marta; Leja, Wiktoria; Błaszczak, Maciej; Latalska, Katarzyna; Pastuszak, Andżelika; Borkowski, Konrad; Zjawiony, Julia; Zulfiqar, Zeeshan (Quality in Sport, 2026)
Type 2 diabetes mellitus is a chronic metabolic disease that affects over 500 million adults all over the world and represents one of the most important public health challenges of the 21th century. Regular physical activity and structured exercise therapy in particular, is a cornerstone of evidence-based T2DM management. This narrative review synthesizes current evidence on the effects of exercise training on glycemic control and related metabolic, physiological, and psychosocial outcomes in individuals with T2DM, with special emphasis on running as a clinically relevant and globally accessible form of aerobic exercise. A structured literature search was conducted in PubMed, Scopus, and Google Scholar, encompassing publications from the last decade, with particular emphasis on studies published between 2020 and 2026. Evidence from meta-analyses and randomized controlled trials consistently demonstrates that structured aerobic exercise produces significant reductions in glycated haemoglobin (HbA1c) and fasting blood glucose. Additionally, prospective cohort study data found running to significantly reduce the risk of developing T2DM by 28%. Studies have also reported a dose response relationship when examining performed run by duration, frequency, distance, and speed. Molecular mechanisms responsible for the glycemic improvements due to exercise include AMPK mediated GLUT4 translocation into skeletal muscle cells, changes in post translational modification to insulin signaling proteins, and increased mitochondrial biogenesis. In addition to improving glycemia, regular exercise has been shown to decrease both visceral and hepatic ectopic fat, improve multiple cardiometabolic risk factors, and produce psychologically relevant advantages including reduced symptoms of depression and anxiety. Therefore, exercise therapy, using running as one of its most accessible and effective forms, provides advantageous approach to managing all aspects of T2DM.